Dampak integrasi pembelajaran berbasis masalah dan inkuiri pada pemahaman konsep matematis - Sulistyorini, Yunis; Yazidah , Nok Izatul (International Journal of Progressive Mathematics Education, 2025)
Purpose: This study aims to enhance students' mathematical conceptual understanding through the integration of Problem-Based Learning (PBL) and Inquiry models. This approach is implemented to mitigate the constraints of teacher-centered procedural learning and to foster higher-order thinking skills. Design/methodology/approach: Utilizing a two-cycle Classroom Action Research (CAR) design, the study involved Mathematics Education students. Data were comprehensively collected via conceptual understanding tests, activity observation sheets, and student response questionnaires to evaluate the intervention's effectiveness.Findings: The findings indicate a significant improvement in the mean conceptual understanding scores from Cycle I to Cycle II. The integration proved effective in actively engaging students across five stages—problem orientation, hypothesis formulation, investigation, concept analysis, and presentation—thereby rendering the learning process more meaningful.Practical implications: These results recommend the adoption of the integrated PBL-Inquiry syntax by educators to facilitate student autonomy in solution-finding and to reinforce the retention of mathematical concepts.Originality/value: This study presents a pedagogical framework that synergizes the depth of inquiry with the contextual relevance of PBL, serving as a robust strategy to address conceptual difficulties.   Purpose: Penelitian ini bertujuan meningkatkan pemahaman konsep matematis peserta didik melalui integrasi model Problem-Based Learning (PBL) dan Inkuiri. Pendekatan ini diterapkan untuk mengatasi kendala pembelajaran prosedural yang berpusat pada guru dan mengembangkan keterampilan berpikir tingkat tinggi. Design/methodology/approach: Menggunakan desain Penelitian Tindakan Kelas (PTK) dalam dua siklus, penelitian melibatkan mahasiswa Pendidikan Matematika. Data dikumpulkan secara komprehensif melalui tes pemahaman konsep, lembar observasi aktivitas, dan angket respons peserta didik untuk mengukur efektivitas intervensi.Findings: Temuan menunjukkan peningkatan signifikan rata-rata pemahaman konsep dari siklus I ke II. Integrasi ini terbukti efektif membuat peserta didik lebih aktif dalam lima tahapan: orientasi masalah, perumusan hipotesis, investigasi, analisis konsep, hingga presentasi, menjadikan pembelajaran lebih bermakna.Practical implications: Hasil ini merekomendasikan adopsi sintaks integrasi PBL-Inkuiri bagi pendidik untuk memfasilitasi kemandirian siswa dalam menemukan solusi dan memperkuat retensi konsep matematis.Originality/value: Studi ini menawarkan kerangka kerja pedagogis yang menggabungkan kedalaman inkuiri dengan relevansi kontekstual PBL sebagai strategi ampuh mengatasi kesulitan konseptual.